Efficacy and safety of Tislelizumab combined with Axitinib as first-line treatment for intermediate- and high-risk metastatic clear-cell renal cell carcinoma - Cui, Jie; Xu, Pengyong; Guo, Changying; Guan, Yong; Zhu, Kejia; Ding, Sentai (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of Tislelizumab combined with Axitinib in the treatment of intermediate-high risk metastatic clear-cell renal cell carcinoma (ccRCC).MethodsFrom September 2021 to June 2023, a total of 20 untreated patients with intermediate-high risk metastatic advanced ccRCC from Shandong Provincial Hospital were included in the study. Clinical characteristics and efficacy were analyzed, and adverse events (AEs) were summarized. All patients received Tislelizumab (200 mg every 3 weeks) and Axitinib (5 mg twice daily bid) until disease progression or intolerable toxicity occurred. The primary endpoint was objective response rate (ORR), and secondary endpoints included disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and incidence of adverse reactions (AEs).ResultsThe median follow-up time was 19.0 months (range, 9.2–24.4 months), and the median treatment cycle was 16 (range, 2–16). Partial response was observed in 14 patients (70%), stable disease in 2 patients (10%), and disease progression in 4 patient (20%). The overall ORR was 70.0%, and the DCR was 80.0%. The 1-year OS rate was 100%. The incidence of any grade AEs was 85% (17/20), and the incidence of grade 3–4 AEs was 15% (3/20). Common AEs included gastrointestinal reactions (60%, 12/20), rash (40%, 8/20), and hypertension (30%, 6/20).ConclusionTislelizumab combined with Axitinib as first-line treatment for intermediate-high risk metastatic ccRCC showed significant efficacy and manageable safety.